PERSPECTIVES ON MUSIC EDUCATION IN ESTONIAN SCHOOLS - Kaja, Kadi; Läänemets, Urve; Kiilu, Kristi; Kalamees-Ruubel, Katrin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The content of education at schools meeting the demand for culturally, socially and politically relevant knowledge, skills and competencies for a particular society has remained an issue of debate in all times. Estonia started development of a new national curriculum (NC) in 2020/2021 and both – the content of learning as well as its organization from kindergartens up to the end of gymnasia became a serious issue. The main topic for debates were the proportions of compulsory and optional subjects, especially at the final level (grades 10–12). Music and other art subjects must prove their positions during recent pandemia and military conflicts. The aim of the study is to map expectations of different target groups concerning the future of music education creating the basis for development of music culture in society.The students (n=203) were asked to write essays, analyzing why learning music at high school level is meaningful or not for their personal development. The people responsible for pan-Estonia cultural organizations were interviewed (n=10) and the data were analyzed qualitatively. The results of the study can be used for development of music syllabi in NC of all levels of general education under the present conditions and for teacher training.